Safety and Efficacy of Infusional Perioperative Tacrolimus Therapy in Crohn’s Disease Patients Undergoing Intestinal Resection - Maximilian Beck; Niklas Schomburg; Max Albers; Detlef Bartsch; Niklas Knapp; Jan Granseyer; Thomas Gress; Christian Bauer (Inflammatory Intestinal Diseases)
Introduction: Perioperative optimization of Crohn’s disease (CD) patients is mandatory in order to ensure favorable outcomes and limit perioperative morbidity such as anastomosis-related complications. The use of perioperative tacrolimus may offer beneficial inflammatory control and improve postoperative outcome. However, it also may exhibit unwanted effects of immunosuppression on infectious complications and wound healing. Methods: This is a single-center, retrospective study of CD patients undergoing intestinal resection between 2009 and 2018. Characteristics of CD patients receiving infusional perioperative tacrolimus or not were systematically evaluated and exploratively compared. To investigate the impact of tacrolimus and other predictors on postoperative infectious complications, simple regression with a threshold of p < 0.05 was used. Significant predictors of the simple regression analysis, as well as tacrolimus, were then included into multiple logistic regression. Results: This analysis included 30 patients (34.88%) having received tacrolimus perioperatively and 56 patients (65.12%) that were not treated with tacrolimus. In median, 1 mg/day of tacrolimus was given intravenously for 11 days. Adverse events occurred in 3 patients (10%). The most common adverse events were headache and paresthesia. Tacrolimus showed no significant correlation to postoperative infectious complications. Furthermore, multiple regression analysis found no significant effect of tacrolimus on postoperative infectious complications when controlling for previously identified confounders. Conclusion: Administration of tacrolimus showed no negative impact on postoperative infectious complications in the study cohort, indicating safety of perioperative tacrolimus therapy. By describing in detail our study population of patients receiving perioperative tacrolimus, we provide data guiding future prospective studies.